2002
DOI: 10.1080/00223131.2002.10875215
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Ten Codes Against the Recent GSI Measurements of the Nuclide Yields from208Pb,197Au, and238U + p Reactions at 1 GeV/nucleon

Abstract: A qualitative and quantitative comparison of the recent OSI measurements of the nuclide yields from 208Pb and 238U at 1 OeV/nucleon and 197 Au at 800 MeV/nucleon interactions with protons with the codes LARET (with both IS-ABEL and Bertini options), CEM95, CEM97, CEM2k, CASCADE, CASCADElINPE, YIELDX, RETC, and INUCL is presented The predictive power of these codes is reasonable for nuclides in the near spallation region but is worse for deep spallation and much worse in the fission region. None of these codes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
(9 reference statements)
3
4
0
Order By: Relevance
“…The disagreement increases with increasing distance from the target, and all calculated curves are shifted to the heavy-mass direction, just as was obtained by the authors of the GSI measurements. The results of the CEM97 code are very similar to those of CEM95 (see a figure with CEM97 results in 26) ). Later on, we performed an extensive set of calculations of the same data with several more codes (HETC, 27) LAHET 11) with both ISABEL and Bertini options, CASCADE, 28) CAS-CADE/INPE, 29) INUCL, 30) and YIELDX 23) ) and got very similar results: 26) all codes disagree with the data in the deep spallation region, the disagreement increases as one moves away from the target, and all calculated curves are shifted in the heavy-mass direction.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The disagreement increases with increasing distance from the target, and all calculated curves are shifted to the heavy-mass direction, just as was obtained by the authors of the GSI measurements. The results of the CEM97 code are very similar to those of CEM95 (see a figure with CEM97 results in 26) ). Later on, we performed an extensive set of calculations of the same data with several more codes (HETC, 27) LAHET 11) with both ISABEL and Bertini options, CASCADE, 28) CAS-CADE/INPE, 29) INUCL, 30) and YIELDX 23) ) and got very similar results: 26) all codes disagree with the data in the deep spallation region, the disagreement increases as one moves away from the target, and all calculated curves are shifted in the heavy-mass direction.…”
Section: Resultssupporting
confidence: 71%
“…10,26,31) We find that CEM2k agrees best with these GSI (and ITEP) data of the codes tested here and in. 10,26,31) Finding a good agreement of CEM2k with the isotope production, we wish to see how well it describes spectra of secondary particles in comparison with CEM97. Figure 3 shows examples of neutron spectra from interactions of protons with the same target,…”
Section: Resultssupporting
confidence: 68%
“…We have analyzed with CEM2k and LAQGSM all measurements done at GSI we are acquainted of, both for proton-nucleus and nucleus-nucleus interactions. Some examples of our CEM2k results compared with the GSI data and calculations by other current models for proton-nucleus reactions may be found in 2002), Mashnik et al (2002aMashnik et al ( , 2002cMashnik et al ( , and 2002d, and Titarenko et al (2002). Figure 5 shows an example of LAQGSM results for the reaction p(1 GeV) + 208 Pb compared with GSI data and calculations by a version of LAHET using the INCL event-generator incorporated recently into LAHET.…”
Section: Cem2k and Laqgsmmentioning
confidence: 99%
“…Both codes have been tested against most of the available data and compared with predictions of other modern codes 2002;Mashnik et al, 2002aMashnik et al, -2002dTitarenko et al, 2002). Our comparisons have shown that both codes describe a large variety of spallation, fission, and fragmentation reactions quite reliably and have one of the best predictive powers compared with other available Monte-Carlo codes.…”
Section: Introductionmentioning
confidence: 99%
“…72 The CEM2k and other modules within MCNPX have also been benchmarked for spallation product generation. 73 As part of this research, the combination of MCNPX and CINDER90 in the form of Monteburns is further benchmarked for spallation product generation. In particular, Monteburns is used to simulate spallation product generation in a past experiment at LANSCE at LANL.…”
Section: Spallation Product Generation With Mcnpxmentioning
confidence: 99%